EXERCISE 2D
PAGE NO-90Question 1:
Using factor theorem, show that g(x) is a factor of p(x), when
p(x) = x3 – 8, g(x) = x – 2
Answer 1:
Let:
p(x) = x3 – 8
Now,
By the factor theorem, (x – 2) is a factor of the given polynomial if p(2) = 0.
Thus, we have:
Hence, (x 2) is a factor of the given polynomial.
Question 2:
Using factor theorem, show that g(x) is a factor of p(x), when
p(x) = 2x3 + 7x2 – 24x – 45, g(x) = x – 3
Answer 2:
Let:
p(x) = 2x3 + 7x2 – 24x – 45
Now,
By the factor theorem, (x 3) is a factor of the given polynomial if p(3) = 0.
Thus, we have:
Hence, (x 3) is a factor of the given polynomial.
Question 3:
Using factor theorem, show that g(x) is a factor of p(x), when
p(x) = 2x4 + 9x3 + 6x2 – 11x – 6, g(x) = x – 1
Answer 3:
Let:
p(x) = 2x4 + 9x3 + 6x2 – 11x – 6
Here,
By the factor theorem, (x 1) is a factor of the given polynomial if p(1) = 0.
Thus, we have:
Hence, (x 1) is a factor of the given polynomial.
Question 4:
Using factor theorem, show that g(x) is a factor of p(x), when
p(x) = x4 – x2 – 12, g(x) = x + 2
Answer 4:
Let:
p(x) = x4 – x2 – 12
Here,
By the factor theorem, (x + 2) is a factor of the given polynomial if p (2) = 0.
Thus, we have:
Hence, (x + 2) is a factor of the given polynomial.
Question 5:
Using factor theorem, show that g(x) is a factor of p(x), when
p(x) = 69 + 11x – x2 + x3, g(x) = x + 3
Answer 5:
Putting x = −3 in p(x), we get
Therefore, by factor theorem, (x + 3) is a factor of p(x).
Hence, g(x) is a factor of p(x).
Question 6:
Using factor theorem, show that g(x) is a factor of p(x), when
p(x) = 2x3 + 9x2 – 11x – 30, g(x) = x + 5
Answer 6:
Let:
Here,
By the factor theorem, (x + 5) is a factor of the given polynomial if p (5) = 0.
Thus, we have:
Hence, (x + 5) is a factor of the given polynomial.
Question 7:
Using factor theorem, show that g(x) is a factor of p(x), when
p(x) = 2x4 + x3 – 8x2 – x + 6, g(x) = 2x – 3
Answer 7:
Let:
Here,
By the factor theorem, (2x 3) is a factor of the given polynomial if .
Thus, we have:
Hence, (2x 3) is a factor of the given polynomial.
Question 8:
Using factor theorem, show that g(x) is a factor of p(x), when
p(x) = 3x3 + x2 – 20x + 12, g(x) = 3x – 2
Answer 8:
Putting in p(x), we get
Therefore, by factor theorem, (3x − 2) is a factor of p(x).
Hence, g(x) is a factor of p(x).
Question 9:
Using factor theorem, show that g(x) is a factor of p(x), when
Answer 9:
Let:
Here,
By the factor theorem, is a factor of the given polynomial if
Thus, we have:
Hence, is a factor of the given polynomial.
Question 10:
Using factor theorem, show that g(x) is a factor of p(x), when
Answer 10:
Let:
Here,
By the factor theorem, will be a factor of the given polynomial if = 0.
Thus, we have:
Hence, is a factor of the given polynomial.
Question 11:
Show that (p – 1) is a factor of (p10 – 1) and also of (p11 – 1).
Answer 11:
Let f(p) = p10 – 1 and g(p) = p11 – 1.
Putting p = 1 in f(p), we get
f(1) = 110 − 1 = 1 − 1 = 0
Therefore, by factor theorem, (p – 1) is a factor of (p10 – 1).
Now, putting p = 1 in g(p), we get
g(1) = 111 − 1 = 1 − 1 = 0
Therefore, by factor theorem, (p – 1) is a factor of (p11 – 1).
Question 12:
Find the value of k for which (x − 1) is a factor of (2x3 + 9x2 + x + k).
Answer 12:
Let:
Hence, the required value of k is 12.
Question 13:
Find the value of a for which (x − 4) is a factor of (2x3 − 3x2 − 18x + a).
Answer 13:
Let:
Hence, the required value of a is 8.
Question 14:
Find the value of a for which (x + 1) is a factor of (ax3 + x2 – 2x + 4a – 9).
Answer 14:
Let f(x) = ax3 + x2 – 2x + 4a – 9
It is given that (x + 1) is a factor of f(x).
Using factor theorem, we have
f(−1) = 0
Thus, the value of a is 2.
Question 15:
Find the value of a for which (x + 2a) is a factor of (x5 – 4a2 x3 + 2x + 2a +3).
Answer 15:
Let f(x) = x5 – 4a2 x3 + 2x + 2a +3
It is given that (x + 2a) is a factor of f(x).
Using factor theorem, we have
f(−2a) = 0
Thus, the value of a is .
Question 16:
Find the value of m for which (2x – 1) is a factor of (8x4 + 4x3 – 16x2 + 10x + m).
Answer 16:
Let f(x) = 8x4 + 4x3 – 16x2 + 10x + m
It is given that is a factor of f(x).
Using factor theorem, we have
Thus, the value of m is −2.
Question 17:
Find the value of a for which the polynomial (x4 − x3 − 11x2 − x + a) is divisible by (x + 3).
Answer 17:
Let:
Now,
By the factor theorem, .
Thus, we have:
Also,
Hence,
Question 18:
Without actual division, show that (x3 − 3x2 − 13x + 15) is exactly divisible by (x2 + 2x − 3).
Answer 18:
Let:
And,
Now, .
For this, we must have:
Thus, we have:
And,
. So, .
Hence, .
Question 19:
If (x3 + ax2 + bx + 6) has (x − 2) as a factor and leaves a remainder 3 when divided by (x − 3), find the values of a and b.
Answer 19:
Let:
Now,
By the factor theorem, we can say:
Now,
Thus, we have:
Subtracting (1) from (2), we get:
a = 3
By putting the value of a in (1), we get the value of b, i.e., 1.
∴ a = 3 and b = 1
Question 20:
Find the values of a and b so that the polynomial (x3 − 10x2 + ax + b) is exactly divisible by (x −1) as well as (x − 2).
Answer 20:
Let:
Now,
By the factor theorem, we can say:
.
Thus, we have:
∴
Also,
By the factor theorem, we can say:
.
Thus, we have:
∴
Putting the value of a, we get the value of b, i.e., 14.
∴ a = 23 and b = 14
Question 21:
Find the values of a and b so that the polynomial (x4 + ax3 − 7x2 − 8x + b) is exactly divisible by (x + 2) as well as (x + 3).
Answer 21:
Let:
Now,
By the factor theorem, we can say:
.
Thus, we have:
∴
Also,
By the factor theorem, we can say:
.
Thus, we have:
∴
Putting the value of a, we get the value of b, i.e., 12.
∴ a = 2 and b = 12
Question 22:
If both (x – 2) and are factors of px2 + 5x + r, prove that p = r.
Answer 22:
Let f(x) = px2 + 5x + r
It is given that (x – 2) is a factor of f(x).
Using factor theorem, we have
Also, is a factor of f(x).
Using factor theorem, we have
From (1) and (2), we have
Question 23:
Without actual division, prove that 2x4 – 5x3 + 2x2 – x + 2 is divisible by x2 – 3x + 2.
Answer 23:
Let f(x) = 2x4 – 5x3 + 2x2 – x + 2 and g(x) = x2 – 3x + 2.
Now, f(x) will be divisible by g(x) if f(x) is exactly divisible by both (x − 1) and (x − 2).
Putting x = 1 in f(x), we get
f(1) = 2 × 14 – 5 × 13 + 2 × 12 – 1 + 2 = 2 – 5 + 2 – 1 + 2 = 0
By factor theorem, (x − 1) is a factor of f(x). So, f(x) is exactly divisible by (x − 1).
Putting x = 2 in f(x), we get
f(2) = 2 × 24 – 5 × 23 + 2 × 22 – 2 + 2 = 32 – 40 + 8 – 2 + 2 = 0
By factor theorem, (x − 2) is a factor of f(x). So, f(x) is exactly divisible by (x − 2).
Thus, f(x) is exactly divisible by both (x − 1) and (x − 2).
Hence, f(x) = 2x4 – 5x3 + 2x2 – x + 2 is exactly divisible by (x − 1)(x − 2) = x2 – 3x + 2.
Question 24:
What must be added to 2x4 – 5x3 + 2x2 – x – 3 so that the result is exactly divisible by (x – 2)?
Answer 24:
Let k be added to 2x4 – 5x3 + 2x2 – x – 3 so that the result is exactly divisible by (x – 2). Here, k is a constant.
∴ f(x) = 2x4 – 5x3 + 2x2 – x – 3 + k is exactly divisible by (x – 2).
Using factor theorem, we have
Thus, 5 must be added to 2x4 – 5x3 + 2x2 – x – 3 so that the result is exactly divisible by (x – 2).
Question 25:
What must be subtracted from (x4 + 2x3 – 2x2 + 4x + 6) so that the result is exactly divisible by (x2 + 2x – 3)?
Question 26:
Use factor theorem to prove that (x + a) is a factor of (xn + an) for any odd positive integer.
Answer 26:
Let f(x) = xn + an
Putting x = −a in f(x), we get
f(−a) = (−a)n + an
If n is any odd positive integer, then
f(−a) = (−a)n + an = −an + an = 0
Therefore, by factor theorem, (x + a) is a factor of (xn + an) for any odd positive integer.
No comments:
Post a Comment